Ta’thīr Ṭarīqah al-Tadrīb (Drill Method) li al-Khaṭ al-ʿArabiy ‘ala Jawdah al-Kitābah laday al-Talāmīż bi Maʿhad Hidayāh al-Nas Bukit Batabuh - Desnely Refrensy; Eka Rizal (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The purpose of this thesis is to know the effect of using the training method (Drill) for Arabic calligraphy on the writing quality of students at Hidayat al-Nas Institute, Bukit Tabbouh, and the training method (Drill) is an attempt to improve Arabic calligraphy. The writing collects data for this research through field research using the experimental method with the quantitative research approach. Experimental research is research that attempts to conduct experiments to test hypotheses. The samples for this research are the Purposive sample. The writer used the experimental research, which is to reveal the promotion of the result of teaching Arabic calligraphy between the experimental class and the control class. As for the method of data collection, it is the test. The writer does the pre- and post-test for the experimental and control chapters, and the writer analyzes the information with aThe purpose of this research is to describe the effect of using the drill method for Arabic calligraphy on the writing quality of students at Hidayat al-Nas Institute, Bukit Batabuah, and the drill method is an attempt to improve Arabic calligraphy. The data collection for this research through field research uses experimental and quantitative research methods. Experimental research is research that attempts to conduct experiments to test hypotheses. The samples for this research are the Purposive sample. The writer used empirical research, which is to reveal the promotion of the result of teaching Arabic calligraphy between the experimental class and the control class. As for the method of data collection, it is the test. The writer does the pre-and post-test for the experimental and control chapters, and the writer analyzes the information with a T-test. The results of learning Arabic calligraphy for students before using this method were the increase in the average of the experimental class was 7.45, and the increase in the standard of the control class was 7.25. The average comparison range between the practical class and the control class is 0.20.الغرض من هذه الدّراسة هو معرفة تأثير استخدام طريقة التدريب (Drill Method) للخط العربي على جودة كتابة التلاميذ بمعهد هداية الناس بوكيت بتابوه. طريقة التدريب (Drill Method) هي أسلوب تنمية العادات وغرسها عند التلاميذ بعملية متكررة على شيئ ما للحصول على البراعة والدقة والكفاءة. تطبيق طريقة التدريب في تعليم الخط العربي من خلال تدريب كتابة الحروف الهجائية التي تقع في بداية الكلمة ووسطها ونهايتها، وكان التدريب متكررا حتى يستطيع الطلاب كتابة الحروف حسب قواعد الخط العربي. يركز الباحثة في هذا البحث على الحروف المعينة التي يخطئ الطلاب كثيرا عند كتابتها. واستخدام طريقة التدريب عبارة عن محاولة تحسين الخط العربي لدى التلاميذ. جمعت الباحثة بيانات هذه الدراسة عن طريق البحث الميداني باستخدام المنهج التجريبي الذي يحاول إجراء التجارب لمعرفة فرق نتائج الطلاب في درس الخط العربي بين الفصل التجريبي والفصل الضابط، ويترتب بعد ذلك اختبار الفرضية؛ مقبولة كانت أو مردودة. أما أسلوب جمع البيانات فهو الاختبار، تقوم الباحثة بالاختبار القبلي والبعدي للفصل التجريبي والفصل الضابط، ثم تحلل الباحثة البيانات باستخدام الاختبار التائي (t-test). بعد تحليل البيانات تتحصل الكاتبة على الاستنتاج أن هناك فرقًا كبيرًا في فعالية بين استخدام طريقة التدريب والطريقة التقليدية لتحسين كتابة الخط العربي لدى التلاميذ بمعهد هداية الناس بوكيت بتابوه. من خلال هذا التحليل، فتثبت الكاتبة أن استخدام طريقة التدريب فعال لتعليم الخط العربي للتلاميذ.